Prospective analysis of the target image of the nurse in the health care area in 2030 - Hernandez Pedroza, Reyna Isabel (2023)
In the clinical practice of nursing, emerge challenges that allow professionals to reflect and motivate themselves by a constant search for improvements that contribute to increase the quality of health care provided to the population of a country, state and/or locality. With this, reflection becomes analysis towards future thinking, where nursing care is in more promising contexts to practice the profession with accessible and feasible ideals. The objective is to prospectively analyze the image of the nursing professional in the health care area in 2030 and to invite reflection on the proposal of this target image shown in this work.